Higher yield sustainability and soil quality by reducing chemical fertilizer with organic fertilizer application under a single-cotton cropping system - Wang, Ning; Zhan, Jin; Feng, Keyun; Qi, Jie; Nan, Hongyu (Frontiers in Plant Science, 2024)
The integrated application of chemical and organic fertilizers has been demonstrated to enhance soil fertility and the sustainable production of cotton yields. However, the impact of different fertilizer formulations on the sustainability of cotton production and soil quality over time have not been widely discussed. Here, we aimed to systematically evaluate the impact of different fertilization regimes [no fertilizer(CK), single application of chemical fertilizer(CF), 75% chemical fertilizer + 25% organic fertilizer (M1), 50% chemical fertilizer + 50% organic fertilizer (M2), 25% chemical fertilizer + 75% organic fertilizer (M3)] on soil quality and yield sustainability in cotton fields in 2023. Results showed that: (1) Compared to the natural state, different fertilization treatments significantly increased the average annual cotton yield and sustainable yield index (SYI) (P< 0.001), with the M1 treatment having the highest yield and the M2 treatment having the highest sustainable yield index (SYI). ( 2) Soil organic matter, soil total nitrogen, soil ammonium nitrogen, soil alkaline dissolved nitrogen, soil available phosphorus, and soil available potassium content showed the highest increase under the M1 treatment as compared to the natural state (P< 0.001). (3) Soil alkaline phosphatase enzyme activity was significantly increased by different fertilization treatments compared to the natural state (P< 0.05), M1, M2 and M3 treatments significantly increased soil urease enzyme activity and soil catalase enzyme activity (P< 0.001). ( 4) The random forest analysis showed that soil organic matter, soil nitrogen fractions (soil total nitrogen, soil ammonium nitrogen, soil alkali-hydrolyzable nitrogen, soil nitrate nitrogen), and available potassium content played a pivotal role in determining the yield and yield sustainability of cotton. (5) The highest soil quality index (SQI) value was observed in the M1. A markedly positive correlation was observed between the SQI and SYI (y = 0.03892x + 0.59609, R 2 = 0.90379, P < 0.001), highlighting that the SQI constituted a significant factor in the sustainable production of cotton. These findings suggest that long-term application of chemical and organic fertilizers is an effective strategy for improving soil quality and cotton yield in continuous cropping while also contributing toward a more sustainable agricultural system.